2018
DOI: 10.12973/eu-jer.7.4.985
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Parents’ Early Literacy Beliefs in the Context of Turkey Through the Parent Reading Belief Inventory (PRBI)

Abstract: This paper aims to test the reliability and validity of the Turkish adaptation of DeBaryshe and Binder's Parent Reading Belief Inventory (PRBI) and to investigate parents' literacy beliefs. The primary focus of this paper is to explore parents' beliefs and practices and their relatedness on the emergent literacy of their children aged 3-7 (M=69.8 months; SD= 9.33 months). As data collection tools, we availed ourselves of the Parent Reading Belief Inventory,(PRBI), Home Literacy Inventory (HLI) and Child Litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
1
4
1
Order By: Relevance
“…The urgency of parental involvement in assisting children's learning from home is to increase children's academic success, where parents can participate in school activities and parents are motivated to be involved in decision-making related to children's academic activities, as well as improve communication between teachers and parents about developmental conditions and learning about children's practical everyday skills (Mcdowell et al, 2018). This is supported by the findings of previous studies that the motivation of parents to be involved in children's activities during learning from home is reading books to children and the intense interaction between parents and children has a positive impact on the development of early literacy in kindergarten age children (Bracken & Fischel, 2008;Powell et al, 2012;Saban et al, 2018). Based on the explanation above, it can be understood the importance of the motivation for parental involvement in children during learning from home.…”
Section: Introductionsupporting
confidence: 52%
“…The urgency of parental involvement in assisting children's learning from home is to increase children's academic success, where parents can participate in school activities and parents are motivated to be involved in decision-making related to children's academic activities, as well as improve communication between teachers and parents about developmental conditions and learning about children's practical everyday skills (Mcdowell et al, 2018). This is supported by the findings of previous studies that the motivation of parents to be involved in children's activities during learning from home is reading books to children and the intense interaction between parents and children has a positive impact on the development of early literacy in kindergarten age children (Bracken & Fischel, 2008;Powell et al, 2012;Saban et al, 2018). Based on the explanation above, it can be understood the importance of the motivation for parental involvement in children during learning from home.…”
Section: Introductionsupporting
confidence: 52%
“…In one study from Turkey, parents' education level and the household income tend to be positively associated with the number of home literacy experiences they provide to their preschool children (Altun, 2019). Consistent with this, another study has found that mothers with higher levels of education are more likely to teach their 3-7-year-old children reading at home than mothers with lower levels of education (Iflazoglu Sabah et al, 2018). In Kazakhstan, Kyrgyzstan, Tajikistan, and Uzbekistan, a large-scale dataset has revealed that the wealthier the families, the greater the number of mother-child interactions (Zainiddinov and Habibov, 2019).…”
Section: What Drives Parents To Engage In Home Literacy and Numeracy mentioning
confidence: 76%
“…Parental literacy belief refers to parental belief in children's literacy achievement due to the parental involvement in school activities, and it is essential in assisting children's literacy development (Saban et al, 2018). Parents can assist their children in early childhood by learning language skills and becoming a literate person using various methods (Katranci et al, 2018).…”
Section: Literacy Beliefs and Environmentmentioning
confidence: 99%
“…Parents who believe that their children's literacy development depends on them will be more likely to spend time and energy to create an atmosphere of literacy with their children (Saban et al, 2018). Support from others will make learning fun and easy for children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation